Desenvolvimento e avaliação do efeito terapêutico de queijos potencialmente probióticos em modelo murino de colite ulcerativa - Bárbara Fernandes Cordeiro (2021)
Functional foods are those that provide a consumer health benefit, in addition to traditional nutritional allegations. In this work, we developed three kinds of cheese and tested the effect of their consumption on murine models of DSS-induced ulcerative colitis. In chapter 1, we used Emmental cheese, a typically French cheese, containing the probiotic bacterium P. freudenreichii 129 in the prevention of acute colitis. The results of this study showed that animals treated preventively with Emmental cheese showed improvements in the symptoms of colitis. In addition, the consumption of probiotic cheese caused a reduction in the secretion of Immunoglobulin A, restored the expression of epithelial barrier genes, and avoided the induction of TNFα, IFNγ, and IL-17. In chapter 2, we developed a functional Prato cheese containing L. casei 01 and tested it in a colitis prevention model, similar to that presented in chapter 1. However, unlike the results of consumption of Emmental cheese, the Prato cheese has not achieved the expected results for the prevention of colitis. In this scenario, we developed a new cheese of the Minas Frescal type, containing the probiotic bacteria L. lactis NCDO 2118. The therapeutic effects of consuming this cheese were tested in a murine model of treatment of colitis induced by DSS. The results of this study, presented in chapter 3, showed that the animals that consumed the Minas Frescal probiotic cheese had a reduction in the severity of the colitis with attenuation of the clinical signs of the disease. In addition, the consumption of this cheese restored the colon's epithelial barrier and modulated the production of pro and anti-inflammatory cytokines. Our study also showed that the addition of probiotic bacteria did not alter the organoleptic characteristics of Minas Frescal cheese and was well accepted by the consumer. Thus, the cheese developed in this work met the minimum requirements to be considered a functional food, opening new perspectives for the development of new functional probiotic foods for personalized nutrition in the context of IBDs.